THE INTERPLAY BETWEEN E-COMMERCE OPTIMIZATION, CONSUMER TRUST, AND IMPULSIVE BUYING IN THAILAND: A COMPREHENSIVE ANALYSIS - Phukhang, Passapol (Finansha: Journal of Sharia Financial Management, 2024)
This study investigates the burgeoning e-commerce market in Thailand, focusing on consumer trust, e-commerce optimization, and impulsive buying behaviors among Generation Z. With a significant portion of Thailand's population engaging in online shopping, the study aims to understand the factors influencing consumer trust and the impact of e-commerce optimization on impulsive buying. Using a quantitative approach, data were collected from 721 respondents aged 18-28 and data analysis using SEM-PLS. The main findings show that e-commerce optimization has a significant positive correlation with consumer trust (R² = 0.965) and impulsive buying (R² = 0.988). This research provides practical contributions for e-commerce practitioners to enhance their marketing and operational strategies based on these findings The results indicate a strong positive correlation between consumer trust and e-commerce optimization, The practical implications of these findings suggest that e-commerce platforms should focus on enhancing their security features and user-friendliness to foster consumer trust, which in turn can lead to increased impulsive buying. Additionally, businesses can utilize these insights to design more effective marketing strategies that leverage consumer trust to drive impulsive purchases. This research provides practical contributions for e-commerce practitioners to enhance their marketing and operational strategies based on these findings. Despite challenges such as consumer trust issues and logistical inefficiencies, the potential for e-commerce growth in Thailand remains substantial, driven by government support and private sector innovation.